Pré-tratamento oxidativo de bagaço de cana com persulfato de sódio para sacarificação enzimática e produção de etanol celulósico - Gonçalves, Lúcio Alexandre Lima [UNESP] (2013)
This thesis focuses on the oxidative pretreatment of sugarcane pulp in view of the enzymatic hydrolysis use for cellulosic ethanol production. It intends to study the sodium persulfate pretreatment in order to obtain an efficient pre‐hydrolyzate for enzymatic saccharification of the pulp. The pulp depolymerization can generate fermentable sugar quantities such as glucose and xylose, and thus substantially increase the amount of ethanol produced by the same sugar cane growing area. Preliminary results indicated that the pretreatment containing sodium persulfate alone can disrupt the pulp at mild temperatures reached during 0.5 min of microwave irradiation, resulting in an increased glucose (124%) and xylose (168%) after enzymatic hydrolysis. The most significant result of glucose (162%) and xylose (265%) was obtained with 3.0 min of microwave irradiation, in an alkaline medium with persulfate. In this pretreatment, an expressive structural modification in the carbonyl region was observed through IR spectrum, besides the less intensive modification in the lignin’s aromatic rings vibration region. The oxidative pretreatment minimized the phenolic inhibitors production, making it undetectable on most experiments. Also, concentrations of furanic derivate from thermal degradation of hemicellulose (furfural) and cellulose (HMF) carbohydrates weren’t detected. Generally, the sodium persulfate pretreatment acts synergistically on the pulp fiber disruption and on the solubilized phenolic oxidation